Aflatoxin in slaughtered broiler livers from an upgraded and a local bird markets in two Local Government Areas of Kaduna State, Nigeria. Issue 2 (2015) - A, Habib M.; P, Abdu; N, Kwanashie C.; J, Kabir; A., Negedu
No abstract available